Assessing the effects of the Sacramento Neighborhood Alcohol Prevention Project (SNAPP) on child abuse and neglect. (January 2023) - Freisthler, Bridget; Thurston, Holly; Price Wolf, Jennifer
Abstract: Background: The role of alcohol use in the etiology of abusive and neglectful parenting is significant. We examined how the Sacramento Neighborhood Alcohol Prevention Project (SNAPP) may have reduced rates of substantiated child maltreatment, entries into foster care, and entries into foster care where alcohol use was a factor. Participants and setting: The study sample is 326 Census block groups: 21 and 16 in the South and North intervention areas, respectively, and 289 in the At-Large comparison area in Sacramento, California. Methods: SNAPP used a quasi-experimental design to reduce alcohol supply and alcohol-related problems among 15–29 year olds in two economically, racially, and ethnically diverse neighborhoods. The dependent variables are substantiated child abuse and neglect; total foster care entries; and alcohol-related foster care entries. Results: Substantiated child abuse and neglect was inconclusive for both intervention areas. In the North, total (RR = 0.822, 95 % CI [0.721, 0.933]) and alcohol-related (RR = 0.760, 95 % CI [0.634, 0.914]) foster care entries decreased by 17.8 % and 24.0 %, respectively. Intervention effects in the South were not well-supported for foster care entries (RR = 1.118, 95 % CI [0.988, 1.258]), but increased alcohol-related foster care entries (RR = 1.264, 95 % CI [1.075, 1.484]). Conclusions: Environmental intervention strategies may be effective at reducing child abuse and neglect. However, given the mixed findings from our work, we need to identify under what conditions these interventions work best and whether some components of these strategies (e.g. awareness vs. enforcement of underage sales) differentially affect child abuse and neglect.